Culture and therapist self-disclosure. (2019) - Phiri, Peter; Rathod, Shanaya; Gobbi, Mary; Carr, Hannah; Kingdon, David
Abstract: Cognitive behaviour therapy (CBT) as a treatment for schizophrenia and psychotic-related disorders has been shown to have significantly greater drop-out rates in clients of black and minority ethnic (BME) groups. This has resulted in poor outcomes in treatments. Our recent qualitative study thus aimed to develop culturally sensitive CBT for BME clients. The study consisted of individual in-depth 1:1 interviews with patients with a diagnosis of schizophrenia, schizo-affective, delusional disorders or psychosis ( n = 15) and focus groups with lay members ( n = 52), CBT therapists ( n = 22) and mental health practitioners ( n = 25) on a data set of 114 participants. Several themes emerged relating to therapist awareness on culturally derived behaviours, beliefs and attitudes that can influence client response and participation in therapy. The current paper aims to explore one of these themes in greater detail, i.e. client-initiated therapist self-disclosure (TSD). Using thematic analysis, the paper highlights key elements of TSD and how this could impact on therapist's reactions towards TSD, the therapeutic alliance and ultimately, the outcomes of therapy. The findings appear to show that TSD has significant relevance in psychological practice today. Some BME client groups appear to test therapists through initiating TSD. It is not the content of TSD they are testing per se, but how the therapist responds. Consequently, this requires therapists' cognisance and sensitive responses in a manner that will nurture trust and promote rapport. Further investigation in this area is suggested with a recommendation for guidelines to be created for clinicians and training. Key learning aims: (1) To develop a dialogue and practice with confidence when addressing issues of self-disclosure with diverse populations. (2) To appreciate the impact therapist self-disclosure has in early stages of engagement, in particular when working with patients from BME communities. (3) To understand the impact and role of self-disclosure as initiated by patients. (4) To increase therapist awareness on cultural differences in self-disclosure and develop ways to address this in therapy. (5) To challenge therapists to adapt psychological therapies to diverse cultures and be cognisant that 'one size does not fit all'.